Pretext, context, hypertext, more text: Libras’ class in music courses from their texts (Orfeu, 2023)
This article aims to reflect on the music teacher’s future formation and its practice in the classroom with deaf students. The Libras is a graduation requirement because functional communication with deaf people is essential to the teaching and learning process. For this reason, educational workers must furnish themselves with this language. For realizing this objective, this research is made by a documental analysis with a quality approach, focusing on examining the Libras course’s essential bibliographical references, teaching curriculum’s definition, and Libras classing course load. Besides, we also explored the objectives presented by Libras’ course in its educational programs taken in music courses by Brazilian degree institutions in order to add more practicing tools to future music teachers.
Keywords: special musical education; teaching formation; deaf people; Libras’ class